Phase 3 solanezumab trials: Secondary outcomes in mild Alzheimer's disease patients. Issue 2 (31st July 2015) - Siemers, Eric R.; Sundell, Karen L.; Carlson, Christopher; Case, Michael; Sethuraman, Gopalan; Liu‐Seifert, Hong; Dowsett, Sherie A.; Pontecorvo, Michael J.; Dean, Robert A.; Demattos, Ronald
Abstract: Introduction: EXPEDITION and EXPEDITION2 were identically designed placebo‐controlled phase 3 studies assessing effects of solanezumab, an antiamyloid monoclonal antibody binding soluble amyloid‐β peptide, on cognitive and functional decline over 80 weeks in patients with mild‐to‐moderate Alzheimer's disease (AD). Primary findings for both studies have been published. Methods: Secondary analyses of efficacy, biomarker, and safety endpoints in the pooled (EXPEDTION + EXPEDITION2) mild AD population were performed. Results: In the mild AD population, less cognitive and functional decline was observed with solanezumab (n = 659) versus placebo (n = 663), measured by Alzheimer's Disease Assessment Scale Cognitive subscale, Mini‐Mental State Examination, and Alzheimer's Disease Cooperative Study–Activities of Daily Living functional scale Instrumental ADLs. Baseline‐to‐endpoint changes did not differ between treatment groups for Alzheimer's Disease Cooperative Study–Activities of Daily Living functional scale, basic items of the ADCS‐ADL, and Clinical Dementia Rating Sum of Boxes. Plasma/cerebrospinal fluid biomarker findings indicated target engagement by solanezumab. Solanezumab demonstrated acceptable safety. Efficacy findings for the moderate AD population are also provided. Discussion: These findings describe solanezumab effects on efficacy/safety measures in a mild AD population. Another phase 3 study, EXPEDITION3, will investigate solanezumab's effects in a mild AD population.